2020
DOI: 10.1186/s13293-020-00285-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in dopamine D1-D2 receptor complex expression and signaling affects depression- and anxiety-like behaviors

Abstract: Depression and anxiety are more common among females than males and represent a leading cause of diseaserelated disability in women. Since the dopamine D1-D2 heteromer is involved in depression-and anxiety-like behavior, the possibility that the receptor complex may have a role in mediating sex differences in such behaviors and related biochemical signaling was explored. In non-human primate caudate nucleus and in rat striatum, females expressed higher density of D1-D2 heteromer complexes and a greater number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 40 publications
1
52
1
1
Order By: Relevance
“…We performed testing in the elevated plus maze as previously described. 43 Animals were placed in the centre square of the maze (head facing an open arm) and allowed to explore for 10 minutes. We recorded behaviour using ANY-maze software (Stoelting Co.), and we measured the number of open- and closed-arm entries and the total time spent in the open and closed arms.…”
Section: Methodsmentioning
confidence: 99%
“…We performed testing in the elevated plus maze as previously described. 43 Animals were placed in the centre square of the maze (head facing an open arm) and allowed to explore for 10 minutes. We recorded behaviour using ANY-maze software (Stoelting Co.), and we measured the number of open- and closed-arm entries and the total time spent in the open and closed arms.…”
Section: Methodsmentioning
confidence: 99%
“…The model was also challenged by the discovery of projecting neurons containing both D 1 and D 2 receptors that may interact to form D 1 –D 2 receptor heteromers in rodents and primates 35–37 . Differential expression of these heteromers, depending on the gender, results in significant changes in protein kinase B/glycogen synthase kinase 3/β‐catenin and brain‐derived neurotrophic factor/tyrosine receptor kinase B signaling pathways, making female more predisposed than male rats to anxiety and depression‐like behavior 38 . As one might expect, the BG motor control circuitry is more complex in primates than in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…A physiological role of D 1 –D 2 receptor heteromers was demonstrated in the healthy brain, and a pathophysiological one in models of addiction [ 11 , 28 , 29 , 30 ]. In addition, the same laboratory has reported that expression differences depending on the sex affect anxiety- and depression-like neuropsychiatric diseases [ 31 ].…”
Section: Features Of Da Receptors That Are Important In Dopaminergmentioning
confidence: 99%